Visceral leishmaniasis in Brazil: scenarios and challenges for the surveillance and control - de Almeida Marzochi, Mauro Celio; Soeiro Barbosa, David; Silva Belo, Vinicius; Rotondo de Araújo, Giovanna; Fagundes da Silva, Aline; Pimentel, Maria Inês; Belizia Feldman Marzochi, Keyla (Revista de Patologia Tropical / Journal of Tropical Pathology, 2023)
Adaptation of the vector and displacement of infected dogs to previously disease-free areas challenges visceral leishmaniasis (VL) control, and leads to geographic dispersion and occurrence in urban and peri-urban areas. Continuous VL control measures over time must be applied with a wide geographic reach, along with better diagnosis practices and timely treatment. The high case-fatality of human VL in areas of recent introduction and its growing association with HIV impose the need for an early diagnosis, treatment and the adoption of active search for human and canine cases incorporated into the routine of periodic home visits by health professionals. The increasing on public rejection of canine euthanasia as a control measure, the limitations of canine therapy with the current available drugs, and the controversies regarding available vaccines for canine protection are discussed. Good prospects on the insecticide-impregnated collars as an effective control measure are emphasized. KEY WORDS: Leishmaniasis; visceral; epidemiology; public health surveillance; Kalazar.